KARAKTERISTIK SOSIOLOGI MASYARAKAT PERAMBAH HUTAN REGISTER 45 SUNAGI BUAYA (Studi di Desa Karya Jaya Kecamatan Mesuji Timur Kabupaten Mesuji) - Ali, Yashinta; Hartoyo, Hartoyo (SOCIOLOGIE, 2013)
Forest with all its fungtion can give benefits and even cause problem or conflict to people. The encroachment of activities undertaken by Resident in state. Owned forests definitely a violation. This violation caused conflict either between people and their environment or conflict with the goverment an citizens. Desire to obtain a decent living land venturing intu the cause of residents in state-owned forests. This research used purpose to know characteristic and activities of encroachers in village Karya Jaya Rural Districts Mesuji Eastern. This research used type of qualitative researcl with data collection techniques through In-depth interviews, observation, and documentations. Result of this research showed that characteristic the encroachers in village Karya Jaya can be looked at trough some of the aspects they are the community forest encroachers chronological Register 45 sungai buaya (the trip encroachers), sosiological characteristics of the forest encroachers Register 45 (cronological villagers, knowledge of residents about status of forest area, purposes of residents to do encroachment), conditions of villagers Karya Jaya (comfort level and health level), the proses of acquiring land (community organizing, land purchase, and to prerare the land), survival strategies (defersifikasi business, compliance clothing, food, and sheiter),community resistance to government policy, and the reasen people survive in the forests of the Register 45 (internal factors and external factors).Keywords: Forest, encroachment, Register 45